Microbial treatment of alcoholic liver disease: A systematic review and meta-analysis - Wang, Qinjian; Shi, Jiangmin; Zhao, Min; Ruan, Gaoyi; Dai, Zebin; Xue, Yilang; Shi, Dibang; Xu, Changlong; Yu, Ouyue; Wang, Fangyan; Xue, Zhanxiong (Frontiers in Nutrition, 2022)
Background and aims Alcoholic liver disease (ALD) is characterized by impaired liver function due to chronic alcohol consumption, even fatal in severe cases. We performed a meta-analysis to determine whether microbial agents have therapeutic potential for ALD and elucidate the underlying mechanisms. Methods and results Forty-one studies were eligible for this meta-analysis after searching the PubMed, Cochrane, and Embase databases. The combined analysis showed that microbial therapy significantly decreased hepatic enzymatic parameters, including alanine transaminase [standardized mean difference (SMD): –2.70, 95% confidence interval (CI): –3.33 to –2.07], aspartate aminotransferase (SMD: –3.37, 95% CI: –4.25 to –2.49), γ-glutamyl transpeptidase (SMD: -2.07, 95% CI: –3.01 to –1.12), and alkaline phosphatase (SMD: –2.12, 95% CI: –3.32 to –0.92). Microbial agents endotoxin to enter the portal circulation and increasing reduced total cholesterol (SMD = -2.75, 95%CI -4.03 to -1.46) and triglycerides (SMD = –2.64, 95% CI: –3.22 to –2.06). Microbial agents increased amounts of the beneficial flora Lactobacillus (SMD: 4.40, 95% CI: 0.97–7.84) and Bifidobacteria (SMD: 3.84, 95% CI: 0.22–7.45), Bacteroidetes (SMD: 2.51, 95% CI: 0.29–4.72) and decreased harmful Proteobacteria (SMD: –4.18, 95% CI: –6.60 to –1.77), protecting the integrity of the intestinal epithelium and relieving endotoxin (SMD: –2.70, 95% CI: -3.52 to –2.17) into the portal vein, thereby reducing the production of inflammatory factors such as tumor necrosis factor-α (SMD: –3.35, 95% CI: –4.31 to –2.38), interleukin-6 (SMD: –4.28, 95% CI: –6.13 to –2.43), and interleukin-1β (SMD: –4.28, 95% CI: –6.37 to –2.19). Oxidative stress was also relieved, as evidenced by decreased malondialdehyde levels (SMD: –4.70, 95% CI: –6.21 to –3.20). Superoxide dismutase (SMD: 2.65, 95% CI: 2.16–3.15) and glutathione levels (SMD: 3.80, 95% CI: 0.95–6.66) were elevated. Conclusion Microbial agents can reverse dysbiosis in ALD, thus significantly interfering with lipid metabolism, relieving inflammatory response and inhibiting oxidative stress to improve liver function.